2016
DOI: 10.1111/1752-1688.12458
|View full text |Cite
|
Sign up to set email alerts
|

Pairing Modern and Paleolimnological Approaches to Evaluate the Nutrient Status of Lakes in Upper Midwest National Parks

Abstract: Understanding what constitutes a reference (background) nutrient condition for lakes is important for National Park Service managers responsible for preserving and protecting aquatic resources. For this study we characterize water quality conditions in 29 lakes across four national parks, and compare their nutrient status to U.S. Environmental Protection Agency (USEPA) nutrient reference criteria and alternative criteria recently proposed by others. Where appropriate we also compare the nutrient status of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…The change in diatom communities in SLBE lakes was less synchronous, and drivers seemed to differ by lake, with some clustering of lakes with similar characteristics. The fact that nutrients were not a common driver across parks is consistent with the findings of VanderMeulen et al (2016), who showed that nutrient conditions in many of the lakes in these parks represent minimally disturbed conditions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The change in diatom communities in SLBE lakes was less synchronous, and drivers seemed to differ by lake, with some clustering of lakes with similar characteristics. The fact that nutrients were not a common driver across parks is consistent with the findings of VanderMeulen et al (2016), who showed that nutrient conditions in many of the lakes in these parks represent minimally disturbed conditions.…”
Section: Discussionsupporting
confidence: 89%
“…Of the shallow lakes, Florence showed turnover along Axis 1 and then a decrease along the conductivity gradient, characterized by an increase in D. stelligera . Both Florence and Bass are considered polymictic, with a medium potential to stratify (VanderMeulen et al, 2016). The increase in D. stelligera in Florence from 2009 to 2014 indicates that the thermocline may have become shallower over that time period (Saros et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The latter difference most likely reflects differences in lake type and water chemistry between the parks [75].…”
Section: Diatom Community Shiftsmentioning
confidence: 99%
“…Little Trout Lake has exhibited a slight shallowing of the thermocline but an extended period of stability in recent decades. At ISRO, the two deep lakes, Siskiwit and Richie, differ in their productivity, basin morphometry, and ecology [75]. Siskiwit is oligotrophic, supports a cold-water fishery, and is much deeper.…”
Section: Diatom Community Shiftsmentioning
confidence: 99%
“…Lake water sampling and analytical methods have been described previously [24,33]. Unfiltered, epilimnetic lake water was sampled two to three times (typically three) per year, between May and September, during most years of the study period.…”
Section: Lake Watermentioning
confidence: 99%